61.2k views
4 votes
Solve x/9 - 1/3 = -5/3. The solution of x is:

User Cadoiz
by
5.1k points

2 Answers

3 votes

Answer:
x=-12

Simplify both sides of the equation


1/9x+-1/3=-5/3

Add 1/3 to both sides


1/9x+-1/3+1/3=-5/3+1/3


1/9x=-4/3

Multiply both sides by 9


9*(1/9x)=9*(-4/3)

Final Answer:
x=-12

User Ray Donnelly
by
4.6k points
5 votes

Answer:

Explanation:


(x)/(9)-(1)/(3) =(-5)/(3)\\\\(x)/(9)=(-5)/(3)+(1)/(3)\\\\(x)/(9)=(-5+1)/(3)\\\\(x)/(9)=(-4)/(3)\\\\x=(-4)/(3)*9\\\\x=-4*3\\\\x=-12

User Axel Scheithauer
by
4.9k points